PENGARUH PENDIDIKAN KEWIRAUSAHAAN, LINGKUNGAN KELUARGA, DAN ATTITUDE TOWARD ENTREPRENEURSHIP TERHADAP MINAT BERWIRAUSAHA ( STUDI KASUS MAHASISWA ADMINISTRASI BISNIS UNIVERSITAS 17 AGUSTUS 1945 SURABAYA) - Hikmah, Lailatul; Andayani, Sri; Mulyati, Diana Juni (Research Journal of Social Science and Economics, 2025)
Abstract This study aims to determine the effect of Entrepreneurship Education, Family Environment, and Attitude Toward Entrepreneurship on Entrepreneurial Interest (Case Study of Students of Universitas 17 Agustus 1945 Surabaya). The research was conducted on all Business Administration students at the University of August 17, 1945. This study uses primary data with questionnaire data collection techniques. This research uses quantitative methods. The data technique used is multiple linear and the sample technique uses a Likert scale. The analysis test is carried out with validity, reliability, classical assumptions, hypothesis testing in which there is a t test and f test. The results of the data analysis test showed that the t test with a significance level of 0.05 resulted in a significance value for the variable entrepreneurship education on entrepreneurial interest of 0.020, the variable family environment of 0.000 and for the variable Attitude Toward Entrepreneurship to Entrepreneurial Interest of 0.000 where the three variables have a value less than the required significance value. So it can be concluded that there is a significant influence between entrepreneurship education, family environment, and attitude toward entrepreneurship on interest in entrepreneurship or it can be said that the hypothesis is accepted. The results of the f test with a significance level of 0.05 resulted in a significance value of 0.000 which is below the required significance value. From the results of the f test, researchers know that the results of the anova hypothesis can be accepted because all independent variables (free) are feasible to explain the dependent variable (bound) analyzed by researchers. The conclusion of this study is that the independent variables of entrepreneurship education, family environment, and attitude toward entrepreneurship partially and simultaneously affect the dependent variable, namely entrepreneurial interest. Keywords: Entrepreneurship education, family environment, attitude toward entrepreneurship, entrepreneurship.